An ex vivo method to evaluate vasoactivity induced by hemoglobin-based oxygen carriers in resistance vessels - Yu, Hang; Gao, Daoyuan; You, Guoxing; Li, Weidan; Wang, Ying; Chen, Yuzhi; Zhao, Lian (Frontiers in Bioengineering and Biotechnology, 2024)
Red blood cell substitutes offer a solution to the problem of blood shortage and side effects of blood transfusion. Hemoglobin based oxygen carriers (HBOCs) is one of the promising substitutes for red blood cells. Vasoactivity, which refers to the side effect of HBOCs to cause vasoconstriction and subsequent hypertension, limits the clinical application of HBOCs. In this study, ex vivo method for the evaluation of vasoactivity induced by HBOCs is established based on isolated rat mesenteric artery vessel and DMT120CP system. DMT120CP system, equipped with flowmeter, permits the control of intravascular pressure, pressure gradient and flow conditions with high accuracy, simulating the physiological conditions for isolated vessels. The concentration of noradrenaline was optimized to 1×10-6 ~ 3×10-6 M. PEGylated bovine hemoglobin (PEG-bHb) was synthesized and perfused into the vessel for vasoactivity evaluation, with bHb as the positive control and PSS buffer solution as the negative control. PEG-bHb showed a hydration diameter of 15.5±1.4nm and a P50 of 6.99 mmHg. PEG-bHb exhibited colloid osmotic pressure of 64.1mmHg and viscosity of 1.73cp at 40 mg/mL. The established vasoactivity evaluation method showed significant differences in samples (bHb or PEG-bHb) with different vasoactivity properties. The vasoconstriction percentage induced by PEG-bHb samples synthesized in different batches showed coefficient of variation values less than 5%, indicating good applicability and repeatability. The established evaluation method can be applied to study the vasoactivity induction and elimination strategies, promoting the clinical application of HBOCs.